A Reappraisal and Reinterpretation of the Satisfaction-Causes-Performance Hypothesis - Organ, Dennis W. (Academy of Management Review, 1977)
Little effort has been given to explaining the logic from which the satisfaction-causes-performance hypothesis came. Such logic may represent an embryonic version of contemporary theories of equity and reciprocity in social exchange. Findings relevant to the hypothesis offer support, if certain qualifying assumptions are made. The hypothesis is reinterpreted in the light of current conceptual approaches.